LITHOLOGICAL INTERPRETATION OF CRUSTAL COMPOSITION IN THE FENNOSCANDIAN SHIELD WITH SEISMIC VELOCITY DATA - Kuusisto M.; Kukkonen I.T.; Heikkinen P.; Pesonen L.J. (My University, 2006)
In this study, we report the results of an investigation of lithological interpretation of the crust in the central Fennoscandian Shield (in Finland) using seismic wide-angle velocity models and laboratory measurements on P- and S-wave velocities of different rock types. The velocities adopted from wide-angle velocity models were compared with laboratory velocities of different rock types corrected for the crustal PT conditions in the study area. The wide-angle velocity models indicate that the P-wave velocity does not only increase step-wise at boundaries of major crustal layers, but there is also gradual increase of velocity within the layers. On the other hand, the laboratory measurements of velocities indicate that no single rock type is able to provide the gradual downward increasing trends. Thus, there must be gradual vertical changes in rock composition. The downward increase of velocities indicates that the composition of the crust becomes gradually more mafic with increasing depth. We have calculated vertical velocity profiles for a range of possible crustal lithological compositions. The Finnish crustal velocity profiles require a more mafic composition than an average global continental model would suggest. For instance, on the SVEKA'81 transect, the calculated models suggest that the crustal velocity profiles can be simulated with rock type mixtures where the upper crust consists of felsic gneisses and granitic-granodioritic rocks with a minor contribution of amphibolite and diabase. In the middle crust, the amphibolite proportion increases. The lower crust consists of tonalitic gneiss, mafic garnet granulite, hornblendite, pyroxenite and minor mafic eclogite. Assuming that these rock types are present in sufficiently extensive and thick layers, they would also have sufficiently high acoustic reflection coefficients for generating the generally well-developed reflectivity in the crust in the central part of the shield. Density profiles calculated from the lithological models suggest that there is practically no density contrast at Moho in areas of the high-velocity lower crust. Comparison of reflectors from FIRE-1 and FIRE-3 transects and the velocity model from SVEKA'81 wide-angle transect indicated that the reflectors correlate with velocity layering, but the three-dimensional structures of the crust complicate such comparisons. © 2006 Elsevier B.V. All rights reserved.
Keywords: CRUST; DENSITY; LITHOLOGY; PETROLOGY; REFLECTIVITY; SEISMIC VELOCITY